Comparison of Backlit and Novel Automated ETDRS Visual Acuity Charts. - Harris, Paul A.; Roberts, Laurel E.; Grant, Rachel (Optometry & Visual Performance, 2018)
Background: This study was conducted to compare two different methods and presentation systems of testing visual acuity to determine whether they are equivalent. Methods: We compared the results of taking visual acuity (VA) measures with the standard backlit Early Treatment of Diabetic Retinopathy Study (backlit ETDRS) and Automated ETDRS (A-ETDRS) VA charts (M&S Technologies, Inc., Niles, IL) on 111 healthy subjects with corrected visual acuity of 20/20 or better. Testing was done under four conditions-- with spectacles, uncorrected, with +1.50 blur over spectacles, and with +3.00 blur over spectacles--to assess correlation of primary outcomes between charts across a wide range of acuity measures. Visual acuity measures were recorded in letter count, logMAR, and standard Snellen measures. Results: Correlations between the backlit ETDRS and the A-ETDRS chart types were 0.93 (uncorrected), 0.60 (with spectacles), 0.76 (+1.50 blur over spectacles), and 0.50 (+3.00 blur over spectacles), with all correlations statistically significant at p< 0.001. Conclusion: This study shows that traditional backlit ETDRS and A-ETDRS charts are functionally equivalent to each other under a variety of testing conditions, mimicking both clinical and research applications. Additional benefits of the automated system over the backlit charts include: the ability to calibrate the system precisely, faster testing and scoring times combined, and less chance for error to enter into the conversion of the raw data into logMAR, letter, or Snellen scores. For all of these reasons, Automated-ETDRS testing is preferred.